Immigrant Unionization through the Great Recession. (April 2013) - Catron, Peter
Previous research has found that in recent years immigrants had a higher propensity to unionize than did native-born workers. However, little research shows that historically marginalized immigrant workers are able to maintain newly acquired union jobs, especially during times unfavorable to unionization more generally. This comment focuses on immigrant unionization during the Great Recession of 2008 to determine whether inroads that immigrants made through organizing were maintained in hostile union environments. Using the Current Population Survey (CPS), I extend Rosenfeld and Kleykamp's (2009) models for Hispanic unionization (which end in 2007) through the recent downturn and beyond. I find that Hispanic immigrants, who held higher odds of union entry or membership in Rosenfeld and Kleykamp's pre-recession analysis, lost union jobs at an increased rate during the Great Recession compared with native-born white workers. These effects for Hispanic immigrants filtered throughout various subcategories and control variables, including years since entry, citizenship status, and nationality. These results are likely not due to immigrants' unfavorable labor market allocation, and to some degree undercut the hopes of those who view immigrants as the key to organized labor's future and organized labor as the key to immigrant prosperity.